Wspólne cechy zwierząt i ludzi w dwunastej księdze "Etymologii" Izydora z Sewilli - Wojciechowski, Leszek Stanisław (Vox Patrum, 2020)
The twelfth book of the Etymologies is, as we know, devoted to the descriptions of animals (divided into eight groups), Isidore of Seville, basing on previous accounts, drew from these sources the most important elements characterizing individual creatures. The twelfth book summarizes the long–lasting (ancient and early Christian) views on the innate corporeal shapes and ways of behaviour and reactions of animals. In the presentation of some animals, the bishop of Seville clearly strengthened (preferred) their features – presented in the sources aviailable to him – which in his interpretation were common to animals and to people, or bore resemblance to human characteristics. He demonstrated features from the psycho-mental and moral spheres (equus, bos, leo, elephantus, canis, simia, iricius, formica, serpens, delfinus). To a lesser degree, he pointed to bodily features (birds, aves: psittacus, pica, coturnix) and social (ciconia, apis). Mention of common (or similar) traits of animals and humans does not occur only in part of the book saying de vermibus (other groups of animals have their ,,representatives” in this regard). Paying attention to the common features of animals and people is, we think, an important aspect of Isidore’s view of the animal world. It is also one of the special features of his anthropology.